2021
DOI: 10.1101/2021.09.09.21263363
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inflammation and nitro-oxidative stress in current suicidal attempts and current suicidal ideation: a systematic review and meta-analysis

Abstract: A meta-analysis showed a significant association between activated immune-inflammatory and nitro-oxidative (IO&NS) pathways and suicide attempts (SA). There is no data on whether suicidal ideation (SI) is accompanied by activated IO&NS pathways and whether there are differences between SA and SI. The current study searched PubMed, Google Scholar, and Web of Science, for articles published from inception until May 10, 2021, and systematically reviewed and meta-analyzed the association between recent SA/… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…Most importantly, based on the above we may conclude that the features of OMDD, including neuroticism, cognitive symptoms of depression, suicidal behaviors, and the phenome of OMDD are at least in part mediated via the immunoneurotoxic effects of different cytokines, chemokine, and growth factors. Previously, it was shown that in different MDD phenotypes, suicidal behaviors and the pure cognitive symptoms of depression, suicidal ideation and attempts were significantly associated with neuro-immune pathways , Vasupanrajit, Jirakran et al 2022, Maes, Rachayon et al 2023.…”
Section: Annotations Of the Immune Profiles In Omddmentioning
confidence: 99%
“…Most importantly, based on the above we may conclude that the features of OMDD, including neuroticism, cognitive symptoms of depression, suicidal behaviors, and the phenome of OMDD are at least in part mediated via the immunoneurotoxic effects of different cytokines, chemokine, and growth factors. Previously, it was shown that in different MDD phenotypes, suicidal behaviors and the pure cognitive symptoms of depression, suicidal ideation and attempts were significantly associated with neuro-immune pathways , Vasupanrajit, Jirakran et al 2022, Maes, Rachayon et al 2023.…”
Section: Annotations Of the Immune Profiles In Omddmentioning
confidence: 99%
“…For categorizing effect sizes, we used SMD values of 0.80, 0.5, and 0.20 to denote large, moderate, and small effects, respectively, following Cohen's guidelines (Cohen 2013). Heterogeneity was assessed through tau-squared statistics, Q, and I 2 values, a method consistent with previous metaanalyses (Almulla, Supasitthumrong et al 2022, Almulla, Thipakorn et al 2022, Almulla, Vasupanrajit et al 2022, Vasupanrajit, Jirakran et al 2022. Meta-regression was employed to identify factors contributing to heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, induction of the TRYCAT pathway in depression is probably not only a consequence of IRS activation but also of increased oxidative stress and increased LPS levels following increased translocation of Gram-negative bacteria [16]. First, there is evidence of increased reactive oxygen (ROS) and nitrogen (RNS) species in depression and suicidal behaviors with increased superoxide, nitric oxide, peroxynitrite, and hydrogen peroxide production [17][18][19]. Such changes not only lead to decreased neurogenesis, neurodegenerative processes, and reduction in brain volume but also to increased staging characteristics as indicated by an increased reoccurrence of illness index (ROI) and suicidal behaviors [19][20][21].…”
Section: The Role Of Cytokines In Triggering Trycat Pathway and Hence...mentioning
confidence: 99%
“…First, there is evidence of increased reactive oxygen (ROS) and nitrogen (RNS) species in depression and suicidal behaviors with increased superoxide, nitric oxide, peroxynitrite, and hydrogen peroxide production [17][18][19]. Such changes not only lead to decreased neurogenesis, neurodegenerative processes, and reduction in brain volume but also to increased staging characteristics as indicated by an increased reoccurrence of illness index (ROI) and suicidal behaviors [19][20][21]. Second, increased gut permeability or leaky gut may cause increased bacterial translocation and thus increased LPS load in the peripheral blood of patients with depression [16].…”
Section: The Role Of Cytokines In Triggering Trycat Pathway and Hence...mentioning
confidence: 99%